Second-generation autologous chondrocyte transplantation: MRI findings and clinical correlations at a minimum 5-year follow-up - Kon, E.; Di Martino, A.; Filardo, G.; Tetta, C.; Busacca, M.; Iacono, F.; Delcogliano, M.; Albisinni, U.; Marcacci, M. (European journal of radiology, 2011)
To evaluate the clinical outcome of hyaluronan-based arthroscopic autologous chondrocyte transplantation at a minimum of 5 years of follow-up and to correlate it with the MRI evaluation parameters. Fifty consecutive patients were included in the study and evaluated clinically using the Cartilage Standard Evaluation Form as proposed by ICRS and the Tegner score. Forty lesions underwent MRI evaluation at a minimum 5-year follow-up. For the description and evaluation of the graft, we employed the MOCART-scoring system. A statistically significant improvement in all clinical scores was observed at 2 and over 5 years. The total MOCART score and the signal intensity (3D-GE-FS) of the repair tissue were statistically correlated to the IKDC subjective evaluation. Larger size of the treated cartilage lesions had a negative influence on the degree of defect repair and filling, the integration to the border zone and the subchondral lamina integrity, whereas more intensive sport activity had a positive influence on the signal intensity of the repair tissue, the repair tissue surface, and the clinical outcome. Our findings confirm the durability of the clinical results obtained with Hyalograft C and the usefulness of MRI as a non-invasive method for the evaluation of the repaired tissue and the outcome after second-generation autologous transplantation over time.